2013
DOI: 10.1021/ja4002376
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Role of Carbon Atoms in Poly(β-amino ester)s for DNA Binding and Gene Delivery

Abstract: Polymeric vectors for gene delivery are a promising alternative for clinical applications as they are generally safer than viral counterparts. Our objective was to further our mechanistic understanding of polymer structure-function relationships to allow rational design of new biomaterials. Utilizing poly(beta-amino ester)s (PBAE), we investigated polymer-DNA binding by systematically varying polymer molecular weight, adding single carbons to the backbone and sidechain of the monomers that compose the polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 30 publications
4
80
0
Order By: Relevance
“…27, 41 This hypothesis is further supported by previous studies, which found that polyplexes formed from polymer consisting of primary amines, such as PLL-g-PEG, have poor transfection efficacy following their major uptake via CvME 40 , while tertiary amines in polymers such as PEI and pDMAEMA enhanced gene transfection via CvME. 34, 35 Also, higher molecular weight PBAE may cause tighter binding to DNA 41, 42 and this may help protect the DNA from premature degradation.…”
Section: Resultsmentioning
confidence: 99%
“…27, 41 This hypothesis is further supported by previous studies, which found that polyplexes formed from polymer consisting of primary amines, such as PLL-g-PEG, have poor transfection efficacy following their major uptake via CvME 40 , while tertiary amines in polymers such as PEI and pDMAEMA enhanced gene transfection via CvME. 34, 35 Also, higher molecular weight PBAE may cause tighter binding to DNA 41, 42 and this may help protect the DNA from premature degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results support previous studies that demonstrated increased PBAE molecular weight does not always improve transfection. 26,27 Collectively, these results suggest translational APC-targeting gene delivery polymers should be designed towards moderately charged and lower molecular weight alternatives.…”
Section: Polyplex Preparation and Characterizationmentioning
confidence: 97%
“…A different approach to reduce cytotoxicity in polycationic vectors was to introduce hydrolyzable linkages, as the ester groups, as applied both to PAMAM 30 itself and to non dendrimeric vectors such as poly(β-amino esters). [31][32][33] Moreover, dendrimers containing amino acid residues 26,[34][35][36] have aroused great interest since the diversity of amino acid moiety can meet the recognized requirement for modulating the buffer capacity of the vector and facilitate its escape from endosomal acidic compartments through membrane disruption of endosomes. 10 On this ground, with the aim of preparing hydrolyzable dendrimer structures which were, at the same time, adequately protonated but also well tolerated by the cells and which could harmonize transfection capacity with a low level of toxicity, we report in this work versatile chemical protocols for the synthesis of a library of 15 dendrimers of fourth, fifth and sixth generation derived from 2,2-bis(hydroxymethyl)propanoic acid (bis-HMPA), a monomer of the AB 2 type used to prepare a variety of dendritic architectures.…”
Section: Introductionmentioning
confidence: 99%